Chemical and dynamical discontinuity at the extratropical tropopause based on START08 and WACCM analyses - Kunz, A. (author); Pan, Laura (author); Konopka, P. (author); Kinnison, Douglas (author); Tilmes, Simone (author) (Journal of Geophysical Research: Atmospheres, 2011)
Using isentropic trace gas gradients of O3 and CO, the discontinuity in the chemical composition of the upper troposphere (UT) and lower stratosphere (LS) is examined on middle world isentropes from 300 to 380 K. The analysis is a follow‐up study of the dynamical discontinuity as represented by the potential vorticity (PV) gradient‐based tropopause, which is based on the product of isentropic PV gradients and wind speed. Overall, there is fairly good consistency between the chemical discontinuity in trace gas distributions and the PV gradient‐based tropopause. Trace gas gradients at the PV gradient‐based tropopause are stronger in winter than in summer, revealing the seasonal cycle of the tropopause transport barrier. The analysis of the trace gas gradients also identifies atmospheric transport pathways in the upper troposphere–lower stratosphere (UTLS). Several regions where trace gas gradients are found to be decoupled from the dynamical field indicate preferred transport pathways between the UT and LS. In particular, anomalous CO and O3 gradients above eastern Africa, eastern Asia, and the West Pacific are likely related to convective transport, and anomalous O3 gradients over the North Atlantic and North Pacific are related to isentropic transport connected to frequent wave breaking. The results indicate that the PV gradient‐based tropopause definition provides a good identification of the dynamical and chemical discontinuity and is therefore effective in locating the physical boundary in the UTLS.